Some nomenclatural adjustments and typifications for almond species in the genus Prunus sensu lato (Rosaceae) - Eisenman, Sasha William (Phytotaxa, 2015)
Prunus dulcis (common almond) is an important horticultural nut crop with an annual production value in the billions of U.S. dollars. The genus Prunus is taxonomically complex, and over the centuries treatments have ranged from splitting the genus into multiple genera, with P. dulcis and relatives being placed in the genus Amgydalus, to having a single, widely circumscribed Prunus s. l. Recent phylogenetic studies based on molecular data support the adoption of a broadly circumscribed Prunus, and the widespread acceptance and usage of Prunus s.l. warrants nomenclatural adjustments for Amygdalus species. Twenty-two new combinations, one nomen novum, and one new nothospecies are proposed. In addition, two lectotypes and three neotypes are here designated.